ANALYZING TEACHER TALK DURING MICROTEACHING: A STUDY IN PRE-SERVICE ENGLISH TEACHER EDUCATION IN INDONESIA - Ika Wahyuni Lestari (Eltin Journal : Journal of English Language Teaching in Indonesia, 2023)
Teacher talk used by pre-service teachers in their microteaching or practice teaching require investigations to identify whether the language pre-service teachers use in teaching is effective. This descriptive qualitative study was conducted to analyze the features of teacher talk uttered by a pre-service English teacher during a microteaching. The subject of the study was Karen (pseudonym), a purposefully selected pre-service teacher who was conducting a 35-minute microteaching as a part of assessment on Microteaching course in one teacher training institution in Yogyakarta, Indonesia in the academic year of 2021/2022. The data in the form of teacher talk’ utterances were collected through Karen’s video-recorded microteaching. The data were analyzed deductively based on FLINT’s analysis model on features of teacher talk. The findings have shown that Karen’s teacher talk aligned with direct and indirect influence. Interestingly, of the features under FLINT system, Karen’s talks did not indicate the use of teacher talk to make requests to students during the learning process. Conclusions and implications are drawn for future directions on studies on classroom analysis and teacher talk.